Rectal eversion and double-stapled ileal pouch anal anastomosis in familial adenomatous polyposis syndrome - Aygar, Muhittin (Int J Surg Case Rep, 2014)
INTRODUCTION: Surgery is the only treatment option for familial adenomatous polyposis (FAP). Aim of surgery in FAP is to minimize colorectal cancer risk without need for permanent stoma. There are especially two operation options; Total colectomy with ileorectal anastomosis (IRA) and total proctocolectomy with ileo-pouch anal anastomosis (IPAA). We report here a patient with FAP who had resection via rectal eversion just over the dentate line under direct visualization and ileoanal-J pouch anastomosis by double-stapler technique. PRESENTATION OF CASE: A 40 yr. old female patient with FAP underwent surgery. Firstly, colon and the rectum mobilized completely, and then from the 10 cm. proximal to the ileo-caecal valve to the recto-sigmoid junction total colectomy was performed. Rectum was everted by a grasping forceps which was introduced through the anus and then resection was performed by a linear stapler just over the dentate line. A stapled J-shaped ileal reservoir construction followed by intraluminal stapler-facilitated ileoanal anastomosis. Follow up at six months anal sphincter function was found normal. DISCUSSION: There is only surgical management option for FAP patients up to now. Total colectomy with IRA and restorative proctocolectomy with IPAA is surgical options for FAP patients that avoid the need for a permanent stoma. Anorectal eversion may be used in the surgical treatment of FAP, chronic ulcerative colitis and early stage distal rectal cancer patients. CONCLUSION: J-pouch ileoanal anastomosis can safely be performed by rectal eversion and double stapler technique in FAP patients.